PENGARUH KETERAMPILAN GURU MEMANFAATKAN TIK DAN GAYA MENGAJAR GURU TERHADAP HASIL BELAJAR DENGAN MENGGUNAKAN BLENDED LEARNING - Dzikrika Bunga Ardika; Sri Zulaihati; Ayatulloh Michael Musyaffi (Yayasan Education and Social Center, 2023)
This study aims to determine the effect of teacher skills in using ICT and teacher teaching styles on student learning outcomes at SMKN 46 Jakarta. The results of this study are: (1) There is a significant positive effect between teachers' skills in using ICT on learning outcomes indicated by the value of t_count 2,165 > t_table 1,98397; (2) There is a significant positive effect between the teacher's teaching style on learning outcomes as indicated by the value of t_count 3,827 > t_table 1,98397; (3) There is a significant positive effect between the skills of teachers in using ICT and the teaching style of teachers on learning outcomes as indicated by the value of nilai f_count 39,4 > f_table 3,09. The multiple correlation coefficient is 0.677 and the coefficient of determination is 0.430 or 43%, the variable of the teacher's skills in using ICT and the teacher's teaching style affect the learning outcomes of students together and the rest is influenced by other factors not examined in this study. Then from this research, it can contribute to the development of the field of education, especially for teachers. Teachers are required to be better and explore more deeply, especially in ICT skills and teaching styles, so that student learning outcomes can experience significant development